2021
DOI: 10.3390/su13042231
|View full text |Cite
|
Sign up to set email alerts
|

How Does Technological Innovation Mediate the Relationship between Environmental Regulation and High-Quality Economic Development? Empirical Evidence from China

Abstract: Technological innovation is considered to be an effective way to promote the quality of economic development and green transition under environmental policies, while the specific mechanism of this process is still unclear. Thus, the purpose of this paper was to examine how technological innovation mediates the relation between environmental regulation and high-quality economic development. Based on the panel data of 34 industries in China from 2007 to 2015, this paper firstly calculated the green total factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The main reason is that, compared with other regions, the Yellow River Basin has special innate natural conditions and acquired social function positioning, and is subject to strong environmental regulations, so the green total factors fluctuate greatly. The conclusion that environmental regulation significantly promotes the growth of GTFP is consistent with most scholars' research, which verifies the establishment of Porter's hypothesis from the perspective of productivity, indicating that pollution control and the improvement of productivity may become a win-win situation [34,35]. However, a considerable number of studies have shown that the high-intensity environmental regulation has an inhibitory effect on industrial GTFP [36,37].…”
Section: Conclusion and Discussionsupporting
confidence: 81%
“…The main reason is that, compared with other regions, the Yellow River Basin has special innate natural conditions and acquired social function positioning, and is subject to strong environmental regulations, so the green total factors fluctuate greatly. The conclusion that environmental regulation significantly promotes the growth of GTFP is consistent with most scholars' research, which verifies the establishment of Porter's hypothesis from the perspective of productivity, indicating that pollution control and the improvement of productivity may become a win-win situation [34,35]. However, a considerable number of studies have shown that the high-intensity environmental regulation has an inhibitory effect on industrial GTFP [36,37].…”
Section: Conclusion and Discussionsupporting
confidence: 81%
“…There have been two main approaches to the characterization of high-quality economic development (HQED): One is to measure by using single indicators such as TFP [16,17], GTFP [7,18,19]. Although GTFP is modified based on the traditional TFP, considering the economic activities by incorporating environmental factors, this method still mainly focuses on the efficiency of economic development, and can't reflect the economic stability and equity.…”
Section: Measurement Of High-quality Economic Developmentmentioning
confidence: 99%
“…Inspired by previous researchers [4,6,19], this study constructs the baseline panel estimates to test the effects of TI on the quantity and quality of economic growth, the detailed specific forms of the estimated models are as follows:…”
Section: Econometric Modelsmentioning
confidence: 99%
“…In their study, Tao Zhu et al used labor productivity (GDP per capita) to express high-quality economic development [14], and Atif Jahanger used total factor productivity to represent high economic quality [15]. Yun Liu et al [16], Die Li and Sumin Hu [17] use green total factor productivity as an indication of high-quality economic development. Nevertheless, a single indicator is frequently unable to convey the complexities of high-quality economic development.…”
Section: Introductionmentioning
confidence: 99%